2021
DOI: 10.3390/ijerph182312432
|View full text |Cite
|
Sign up to set email alerts
|

Health Literacy, Socio-Economic Determinants, and Healthy Behaviours: Results from a Large Representative Sample of Tuscany Region, Italy

Abstract: Background: Health Literacy (HL) is one of the main determinants of health and is crucial for the prevention of noncommunicable diseases, by influencing key health-related behaviours. The aim of the present study was to assess the role of HL and sociodemographic factors in predicting the adoption of two healthy behaviours—physical activity and fruits and vegetables consumption. Methods: This study was conducted on the Tuscan population subsample of the Italian Behavioral Risk Factor Surveillance System in 2017… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
16
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

5
5

Authors

Journals

citations
Cited by 25 publications
(21 citation statements)
references
References 49 publications
2
16
0
3
Order By: Relevance
“…This condition may increase the dissemination of conflicting information and the spread of the infodemic. Moreover, previous cross-national studies about HL showed that Italian adolescents and adults reported lower levels of HL compared with other European countries [58][59][60][61]. These results show the importance of health literacy monitoring to provide inputs for policy and intervention design and developing valid and updated Italian tools to assess health literacy and digital health literacy.…”
Section: Digital Health Literacy Assessmentmentioning
confidence: 56%
“…This condition may increase the dissemination of conflicting information and the spread of the infodemic. Moreover, previous cross-national studies about HL showed that Italian adolescents and adults reported lower levels of HL compared with other European countries [58][59][60][61]. These results show the importance of health literacy monitoring to provide inputs for policy and intervention design and developing valid and updated Italian tools to assess health literacy and digital health literacy.…”
Section: Digital Health Literacy Assessmentmentioning
confidence: 56%
“…The present study considered the data referred to 7157 persons, that is the regional representative sample of Tuscan residents in 2017–2018, which is described elsewhere [ 20 ]. For the purpose of this study only data from residents at high-risk of influenza (3278, 46% of the whole sample) were analysed.…”
Section: Methodsmentioning
confidence: 99%
“…The adherence to various preventive and health-related behaviors has been reported to be positively associated with the level of HL [ 10 , 11 , 12 , 13 , 14 ]. As for COVID-19 preventive measures, to date, only few studies have evaluated the role of HL in influencing the adherence to such behaviors.…”
Section: Introductionmentioning
confidence: 99%